Efeitos de baixos teores de aditivos (TiFe, Fe, TiAl, Nb₂O₅) na cinética de absorção e dessorção de hidrogênio pelo sistema Mg/MgH₂ - Antiqueira, Flávio José (2021)
The hydrogen economy holds great promise in supplying our planet's urgent clean energy needs. The effective and safe hydrogen storage remains a major technological challenge. Thus, the H2 storage in metal hydrides of light materials continues to be pursued. Mg/MgH2 are still extensively researched, but limited by their slow kinetics and high temperatures in the H2 absorption/desorption. In recent works, it was noticed that Mg/MgH2 mixed with additives by the high energy ball milling allows reductions in the absorption/desorption temperatures. Thus, in the first stage of this work, the properties and kinetics of MgH2 processed by reactive milling under H2 (RM) with known additives in low fractions (2 mol% Fe, Nb2O5, TiAl and TiFe), under low temperatures were investigated. MgH2-TiFe showed the best results at 330 °C (desorption) and at low temperatures (absorption). The first H2 absorption was ≈ 2.67 wt.% (1 hour) and ≈ 4.44 wt.% (16 hours) at room temperature (40% and 67% of the maximum theoretical capacity, respectively). The MgH2-TiFe superior performance was attributed to the hydrogen attraction by the created high energy interfaces and to TiFe catalytic action. MgH2-Fe also showed good results, mainly due to the lower desorption temperature than MgH2-TiFe. Thus, in the following stages, it was decided to further investigate the kinetics and the rate limiting mechanisms of H2 reactions in nanocomposites of Mg-8 mol% Fe prepared by reactive milling for 10 and 24 hours. The results showed extremely fast H2 absorption/desorption at 300-350 °C, 10 bar H2 (absorption) and 0.13 bar H2 (desorption). Nanocomposites with MgH2, low Fe fractions and without Mg2FeH6 are suggested as more suitable for H2 storage under mild conditions, and nanocomposites with MgH2 and higher Mg2FeH6 fraction are better for storing thermal-chemical energy under more severe conditions.